If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 12 = 6x + 5 Reorder the terms: 12 + 3x = 6x + 5 Reorder the terms: 12 + 3x = 5 + 6x Solving 12 + 3x = 5 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 12 + 3x + -6x = 5 + 6x + -6x Combine like terms: 3x + -6x = -3x 12 + -3x = 5 + 6x + -6x Combine like terms: 6x + -6x = 0 12 + -3x = 5 + 0 12 + -3x = 5 Add '-12' to each side of the equation. 12 + -12 + -3x = 5 + -12 Combine like terms: 12 + -12 = 0 0 + -3x = 5 + -12 -3x = 5 + -12 Combine like terms: 5 + -12 = -7 -3x = -7 Divide each side by '-3'. x = 2.333333333 Simplifying x = 2.333333333
| 4=16-n | | 4(2x+4)-13= | | 5x^3+21x^2-21x+5=0 | | 5(n+8)=10 | | 5x^2-5x-30=30 | | 50t+125=30t+200 | | 5x-x+4x=7-3 | | x+2.75=6 | | 7x-4=6.5 | | 9-6x=4-3x+3x | | 4-2x=14x+15 | | 2t+6=t+8 | | 0.5sin(2x)=cos(x) | | 3(x-2)=2x+16 | | 14=12-10y | | 4(w-9)=6w-38 | | -5n-8(1+n)=-8 | | -16-4y=46 | | 2x^2+20x=22 | | 49x-64x^2=0 | | x^2+0.5x=0.25 | | -8x+13=-3(x-6) | | x^2-0.5x-0.25=0 | | x^2+0.5x-0.25=0 | | -3y-2(-7+5x)=12 | | x^2+0.5x-2.5=0 | | 9y-5(y+2)-3= | | 65x+10=55x-100 | | -3x-2(-7+5y)=12 | | 56X^2-103X+45=0 | | 2x+3x+8x=78 | | 8+8x=x+8 |